Structure and Optical Properties of Doped SiO2 Mesoporous Glasses - G. Hernández-Padrón; M. Hernández-Ortiz; H. A. Durán-Muñoz; M. García-Garduño; V. M. Castaño (Journal of Nanotechnology)
Monolithic mesoporous silica glasses were synthesized. The presence of Cu2+ and Fe3+ cations during the synthesis of sol-gel precursors leads to different morphologies and pore sizes. The materials are characterized via IR and Raman scattering spectra to detect surface groups and -Si-O-Si- rings (i.e., 3–6 Si atoms) and morphology is examined through electron microscopy. N2 sorption isotherms reveal details of the mesoporous structure of the materials, which are endowed with significantly large surface areas and pore volumes. Vapor percolation occurs in these samples because of a void arrangement consisting of pore bulges delimited by narrower necks. The optical characterization shows the luminescence spectrum and thermoluminescent behavior subjected to successive exposures of beta particles.